2009
DOI: 10.1093/her/cyp036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a single computer-tailored e-mail for smoking cessation: results after 6 months

Abstract: To date, few Internet-delivered smoking cessation interventions have been tested. This study tested the efficacy, understandability, credibility and personal relevance of an e-mail-delivered computer-tailored smoking cessation intervention. It included tailored action plan feedback, as recent studies have demonstrated the importance of planning in facilitating quitting smoking. Participants (Dutch adults) were randomly assigned to the intervention (computer-tailored e-mail; N = 224) or the control group (gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
212
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(222 citation statements)
references
References 59 publications
8
212
0
2
Order By: Relevance
“…Similar with other studies (Diskstra et al, 1998;Te Poel et al, 2009;Smit et al, 2012), around 19% of the participants did not fill in the process evaluation questionnaire and the results are based only on self reported data. The intervention did not provide medical treatment, only counselling, but it offered information about way they could get more medical advice and help.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Similar with other studies (Diskstra et al, 1998;Te Poel et al, 2009;Smit et al, 2012), around 19% of the participants did not fill in the process evaluation questionnaire and the results are based only on self reported data. The intervention did not provide medical treatment, only counselling, but it offered information about way they could get more medical advice and help.…”
Section: Discussionsupporting
confidence: 85%
“…The tailored intervention was based on previously developed computer-tailored smoking cessation interventions (Diskstra et al, 1998;Te Poel et al, 2009;Smit et al, 2012) while the I-Change model served as the theoretical framework (De Vries et al, 2003). A library with messages which might be needed was created.…”
Section: Characteristics Of the Computer Tailored Smoking Cassation Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with trial‐based economic evaluations of internet‐based smoking cessation interventions 15, 17, 24, 55, this study showed some benefits of using such interventions in the short term. It is important, however, to note that trial‐based studies may not capture long term cost‐effectiveness, as the impact of cessation may need longer than a 12‐month follow‐up to improve QALYs of the ex‐smokers 24, 56.…”
Section: Discussionsupporting
confidence: 81%